Modern teaching methods with computer games in the educational process - Shavkieva Dilfuza Shakarboevna (Genius Journals, 2021)
This article is about the emotional activity of learning English, the ability to learn the language, the level of development of competencies, the development of teaching and methodological guidelines, recommendations for their application in the learning process, the analysis of their effectiveness. The step-by-step logical structure of the English text is called a logical algorithm. The logical algorithm serves as a basic guide in achieving the goal in the study of teaching material in English, that is, in understanding the content of the material
Keywords: Clothing; Technology; Style; Equipment